Methodology, deployment, and performance of pico balloons in Antarctica - McKinney, Todd (LOUIS, 2024)
During the 2022/2023 Antarctic summer, eight pico balloon flights from Neumayer Station III unveiled insights into Antarctic troposphere/stratospheric winds (9 - 15 km AMSL). The most impressive flight lasted an astounding 98 days, completing eight circumnavigations of the Southern Hemisphere. Flight data indicated zonal velocities from -50 to 250 km/hr and meridional velocities of ±100 km/hr, with total wind speeds from 2.0 to 270 km/hr. Pico balloons can ascend due to convection, altering their float density. They also drift further south than larger stratospheric balloons, reaching latitudes close to the south pole. This study showcases the transformation of budget-friendly party balloons into effective research tools, emphasizing their logistical simplicity: all materials except lifting gas were transported to Antarctica in one person’s carry-on. The work promotes pico balloons’ wider scientific application.